A Multicultural Approach in Islamic Education Learning to Strengthen the Islamic Identity of Moderate Students in PTKIN Aceh - Idris, Tasnim; Rijal, Fakhrul; Irwandi; Hanum, Rafidhah; Mardhiah, Ainal (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This research project investigates the challenges of religious tolerance and radicalism in Indonesia, focusing on university students and the context of conservative shifts. This study examines the approach the State Islamic University (UIN) in Aceh utilized to advance a moderate interpretation of Islam, integrating multicultural-based Islamic Religious Education. The study employs a qualitative methodology, including in-depth interviews and participatory observation. The findings illustrate that UIN Aceh has adapted its curriculum to integrate multicultural values to foster religious tolerance among students. The influence of lecturers who espouse moderate attitudes and the active engagement of students in activities that promote diversity have been demonstrated to be effective in reducing radical tendencies. The research underscores the necessity of continuously assessing the strategy's effectiveness and emphasizes the importance of multicultural-based learning in fostering students' appreciation of diverse perspectives. Ultimately, this multicultural approach is expected to shape individuals who are morally upright, tolerant, and capable of collaboration in a diverse society. The study's outcomes offer valuable insights for other educational institutions in devising strategies to encourage tolerance and curb student radicalism.